2017
DOI: 10.3390/ijms18071517
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Cell Death 1 (PD-1) and Cytotoxic T Lymphocyte-Associated Antigen 4 (CTLA-4) in Viral Hepatitis

Abstract: Virus-specific cluster of differentiation 8 (CD8+) cytotoxic T cells (CTL) recognize viral antigens presented on major histocompatibility complex (MHC) class I chains on infected hepatocytes, with help from CD4+ T cells. However, this CTL response is frequently weak or undetectable in patients with chronic hepatitis B virus (HBV) and hepatitis C virus (HCV) infection. Programmed cell death 1 (PD-1) and cytotoxic T lymphocyte-associated antigen 4 (CTLA-4) are receptors in the CD28 family of costimulatory molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 135 publications
1
67
0
Order By: Relevance
“…High expressions are generally believed to be markers of exhausted T cells during the chronic stage. While previous studies and reviews concentrated on “classical” ICs of PD‐1 and CTLA‐4, emerging studies unravel crucial roles of “the next generation” ICs of TIGIT, LAG‐3, BTLA, and other ICs in chronic viral infections, which will be the focus of this section.…”
Section: The Regulation Of Multiple Ics During Chronic Hbv and Hcv Inmentioning
confidence: 94%
“…High expressions are generally believed to be markers of exhausted T cells during the chronic stage. While previous studies and reviews concentrated on “classical” ICs of PD‐1 and CTLA‐4, emerging studies unravel crucial roles of “the next generation” ICs of TIGIT, LAG‐3, BTLA, and other ICs in chronic viral infections, which will be the focus of this section.…”
Section: The Regulation Of Multiple Ics During Chronic Hbv and Hcv Inmentioning
confidence: 94%
“…12 Studies showed that the upregulation of PD-1 is associated with T cell exhaustion and persistent viral infection. 13 Our past study showed that in PEG-IFN-α therapy responders, PD-1 levels decreased in CD4 + and CD8 + T cells from peripheral blood, while in non-responders, CD4 + PD-1 + T and CD8 + PD-1 + T cells had no signi cant reduction. 6 In this study, CD8 + PD-1 + T cells signi cantly decreased in liver tissue in the FIER group after treating with PEG-IFN-α for 6 months, while CD8 + PD-1 -T cells did not change signi cantly.…”
Section: Discussionmentioning
confidence: 95%
“…Immune dysregulation regulates almost the whole process of HBV‐associated liver diseases including HCC, especially with T‐cell dysfunction in patients overexpressing PD‐1 and CTLA‐4 . The phenomenon that PD‐1 and CTLA‐4 are up‐ or downregulated along with virus relapse or recovery indicates that they have protective effects that involve suppressing cytotoxic T cells, which induce the harmful destruction of infected hepatocytes in self‐limited viral hepatitis.…”
Section: Immune Checkpoint Levels According To Clinical Diseases Of Cmentioning
confidence: 99%